Step by step Microsoft Office Excel 2007 - Fyre, Curtis, 1968- (Microsoft Step by step)
Summary: Experience learning made easy and quickly teach yourself how to organize, analyze, and present data with Excel 2007. With Step By Step, you set the pace building and practicing the skills you need, just when you need them! Create formulas, calculate values, and analyze data. Present information visually with graphics, charts, and diagrams, Build PivotTable dynamic view seven easier with new data tables. Reuse information from databases and other documents, Share spreadsheets for review and manage changes. Create macros to automate repetitive tasks and simplify your work. Your all-in-one learning experience.